Implementasi Program Pemberdayaan Ekonomi Masyarakat Pesisir di Kelurahan Mangunharjo Kecamatan Tugu Kota Semarang - Sefryan Ardi Saputra; Margaretha Suryaningsih; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2014)
The Program of Coastal Society Economic Empowerment Manguharjo District, Tugu Sub – District, Semarang City is due to by the still high number of poverty in coastal Mangunharjo District. Therefore, the Marine and Fisheries Agency of the city of Semarang was trying to improve the economy of coastalsociety by digging and empowering potential Mangunharjo District. The Program is grounded by a decision of the Minister of Marine and Fisheries No. 18 of 2004 concerning the implementation of the General guidelines for economic Coastal Society Economic Empowerment Program.The purpose of this research is to investigate the implementation process and the factors that affect Coastal Society Economic Empowerment Program. The purpose of this program can be achieved if the implementation of Coastal Society Economic Empowerment Program follow Riant Nugroho criteria that Policy Accuracy, Precision of execution, the target accuracy, precision and accuracy of the process environment. Implementation of Coastal Society Economic Empowerment can not be separated from the factors supporting and inhibiting factors. Based on the theory of George C. Edwards III, factors supporting and inhibiting factors is communication, bereaucratic structure, resources and disposition.The results of this study indicate that the Departement of Marine and Fisheries Semarang City was ready to implement the Coastal Society Economic Empowerment Program in District Mangunharjo. Implementation of Coastal Society Economic Empowerment has been implemented properly. Factors thainfluence is (1) a good implementor ability to deliver information, (2) clarity of information recevied by the public, (3) good impementor commitment in implementing the program, (4) the use of the authority vested in implementor the fullest.